RNA Splicing of FLC Modulates the Transition to Flowering - Qi, Hao-Dong; Lin, Yi; Ren, Qiu-Ping; Wang, Yu-Yi; Xiong, Feng; Wang, Xiu-Ling (Frontiers in Plant Science, 2019)
Flowering is a critical stage of plant development and is closely correlated with seed production and crop yield. Flowering transition is regulated by complex genetic networks in response to endogenous and environmental signals. FLOWERING LOCUS C (FLC) is a central repressor in the flowering transition of Arabidopsis thaliana. The regulation of FLC expression is well studied at transcriptional and post-transcriptional levels. A subset of antisense transcripts from FLC locus, collectively termed cold-induced long antisense intragenic RNAs (COOLAIR), repress FLC expression under cold exposure. Recent studies have provided important insights into the alternative splicing of COOLAIR and FLC sense transcripts in response to developmental and environmental cues. Herein, at the 20th anniversary of FLC functional identification, we summarise new research advances in the alternative splicing of FLC sense and antisense transcripts that regulates flowering.